Three Simple Hepatic Cysts Successfully Managed Using a Laparoscopic Approach - Manakijsirisuthi, Wanchai (The Thai Journal of Surgery, 2021)
Hepatic cysts are not an uncommon condition, and most are simple cysts, which cause no symptoms and are usually diagnosed incidentally during imaging for other diseases. However, problems may occur if they grow above a certain size. Complications, such as hemorrhage, infection or rupture are rare, but can be life-threatening or emergency conditions. The author reported three cases of simple hepatic cysts, each with a different clinical presentation. The first patient presented as an emergency condition due to ruptured hepatic cyst. The second patient was asymptomatic and was incidentally diagnosed while imaging for gallstones. The last patient had symptoms of pressure effect from a large cyst. All patients could be managed by a laparoscopic approach without conversion to open surgery.